A calculus problem by 敬全 钟

Calculus Level 4

1 1 + 1 2 1 3 1 4 + 1 5 + 1 6 1 7 1 8 + \large \dfrac{1}{1}+\dfrac{1}{2}-\dfrac{1}{3}-\dfrac{1}{4}+\dfrac{1}{5}+\dfrac{1}{6}-\dfrac{1}{7}-\dfrac{1}{8}+\cdots

If the closed form of the sum above can be expressed as π + ln ( a ) a \dfrac{\pi+\ln (a)}{a} , where a a is a positive integer, find a a .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

This is essentially the composition of two series that is, n = 0 ( 1 ) n 2 n + 1 = π 4 \displaystyle \sum_{n=0}^\infty \dfrac{(-1)^n}{2n+1} = \dfrac{\pi} {4} which is the series for tan 1 x \tan^{-1} x .

The other one is :

n = 1 ( 1 ) n 1 n = ln 2 \displaystyle \sum_{n=1}^\infty \dfrac{(-1)^{n-1}}{n}=\ln 2

Adding the first and half of the second we get the desired series and the result is π + ln 4 4 \dfrac{\pi+\ln 4}{4} which makes the answer 4 \boxed{4}

Kushal Bose
May 19, 2017

The above expression can be written as

r = 0 ( 1 4 r 3 + 1 4 r 2 1 4 r 1 1 4 r ) \displaystyle \sum_{r=0}^{\infty} (\dfrac{1}{4r-3}+\dfrac{1}{4r-2}-\dfrac{1}{4r-1}-\dfrac{1}{4r})

= r = 0 0 1 ( x 4 r 4 + x 4 r 3 + x 4 r 2 + x 4 r 1 ) d x =\displaystyle \sum_{r=0}^{\infty} \int_{0}^{1} (x^{4r-4}+x^{4r-3}+x^{4r-2}+x^{4r-1})dx

= 0 1 ( r = 0 ( x 4 r 4 + x 4 r 3 x 4 r 2 x 4 r 1 ) ) d x =\displaystyle \int_{0}^{1} (\sum_{r=0}^{\infty} (x^{4r-4}+x^{4r-3}-x^{4r-2}-x^{4r-1}))dx

= 0 1 ( 1 1 x 4 + x 1 x 4 x 2 1 x 4 x 3 1 x 4 ) d x =\displaystyle \int_{0}^{1} (\dfrac{1}{1-x^4} + \dfrac{x}{1-x^4} - \dfrac{x^2}{1-x^4}-\dfrac{x^3}{1-x^4}) dx

= 0 1 1 + x 1 + x 2 d x = π + ln ( 4 ) 4 =\displaystyle \int_{0}^{1} \dfrac{1+x}{1+x^2} dx \\ =\dfrac{\pi+\ln (4)}{4}

Chew-Seong Cheong
May 12, 2017

Consider Maclaurin series of the following:

ln ( 1 x ) = x + x 2 2 + x 3 3 + x 4 4 + + x 5 5 + x 6 6 + x 7 7 + x 8 8 Putting x = i ln ( 1 i ) = i + i 2 2 + i 3 3 + i 4 4 + i 5 5 + i 6 6 + i 7 7 + i 8 8 + Dividing both sides by i ln ( 1 i ) i = 1 + i 2 + i 2 3 + i 3 4 + i 4 5 + i 5 6 + i 6 7 + i 7 8 + i ln ( 1 i ) = 1 + i 2 1 3 i 4 + 1 5 + i 6 1 7 i 8 + \begin{aligned} - \ln (1-x) & = x + \frac {x^2}2 + \frac {x^3}3 + \frac {x^4}4 + + \frac {x^5}5 + \frac {x^6}6 + \frac {x^7}7 + \frac {x^8}8 \cdots & \small \color{#3D99F6} \text{Putting }x = i \\ - \ln (1-i) & = i + \frac {i^2}2 + \frac {i^3}3 + \frac {i^4}4 + \frac {i^5}5 + \frac {i^6}6 + \frac {i^7}7 + \frac {i^8}8 + \cdots & \small \color{#3D99F6} \text{Dividing both sides by }i \\ - \frac {\ln (1-i)}i & = 1 + \frac i2 + \frac {i^2}3 + \frac {i^3}4 + \frac {i^4}5 + \frac {i^5}6 + \frac {i^6}7 + \frac {i^7}8 + \cdots \\ i\ln (1-i) & = 1 + \frac i2 - \frac 13 - \frac i4 + \frac 15 + \frac i6 - \frac 17 - \frac i8 + \cdots \end{aligned}

Therefore, we have:

S = 1 + 1 2 1 3 1 4 + 1 5 + 1 6 1 7 1 8 + = [ i ln ( 1 i ) ] + [ i ln ( 1 i ) ] = [ i ln ( 2 e π 4 i ) ] + [ i ln ( 2 e π 4 i ) ] = [ i ( ln 2 2 π 4 i ) ] + [ i ( ln 2 2 π 4 i ) ] = [ π 4 + ln 2 2 i ] + [ π 4 + ln 2 2 i ] = π 4 + ln 2 2 = π 4 + ln 4 4 \begin{aligned} S & = 1 + \frac 12 - \frac 13 - \frac 14 + \frac 15 + \frac 16 - \frac 17 - \frac 18 + \cdots \\ & = \Re [i\ln (1-i)] + \Im [i\ln (1-i)] \\ & = \Re \left[i \ln \left(\sqrt 2 e^{-\frac \pi 4i} \right) \right] + \Im \left[i \ln \left(\sqrt 2 e^{-\frac \pi 4i} \right) \right] \\ & = \Re \left[i \left(\frac {\ln 2}2 -\frac \pi 4i \right) \right] + \Im \left[i \left(\frac {\ln 2}2 -\frac \pi 4i \right) \right] \\ & = \Re \left[\frac \pi 4 + \frac {\ln 2}2i \right] + \Im \left[\frac \pi 4 + \frac {\ln 2}2i \right] \\ & = \frac \pi 4 + \frac {\ln 2}2 = \frac \pi 4 + \frac {\ln 4}4 \end{aligned}

a = 4 \implies a = \boxed{4}

For the first line, if -1<x <=1 is true, then x=i does not fall under this range.

Pi Han Goh - 4 years ago

Log in to reply

I was trying to resolve this but don't know how.

Chew-Seong Cheong - 4 years ago

Log in to reply

The issue is here is that you started with the geometric progression sum , 1 1 x = 1 + x + x 2 + \frac1{1-x} = 1 + x + x^2 + \cdots for 1 < x < 1 -1<x< 1 (and then you integrate it).

After you integrate it, the domain of the function 0 x 1 1 v d v \displaystyle \int_0^x \frac1{1-v} \, dv will still remain 1 < x < 1 -1<x<1 (and might work at the endpoints as well, which can be proven via squeeze theorem ). So you can't say "Oh, I substitute x = i x = i and it just magically works!". To justify that x = i x= i works, you need to show that i = 1 |i|= 1 is at the end point of 1 < x < 1 -1<x<1 , so you got to prove that ln ( 1 x ) = ( what you have written up ) -\ln(1 - x) = (\text{what you have written up}) also converges when x = i x = i first.

I didn't solve it your way, but what I would have done is to convert all the fractions to the form of 0 1 x n d x \int_0^1 x^n \, dx , then summing over all the integrals. You should get Aditya's method.

Addendum:

Note that 1 i = 2 ( 1 2 i 2 ) = 2 cis ( π 4 + 2 π k ) 1 - i = \sqrt 2 \left(\dfrac1{\sqrt2} - \dfrac{i}{\sqrt2} \right) = \sqrt 2 \text{cis}\left( -\dfrac\pi4 + 2\pi k \right) for any integer k k . So there are actually infinitely many values of ln ( 1 i ) \ln(1 - i ) . So, how can you justify that the final value you found is the unique answer?

Pi Han Goh - 4 years ago

Log in to reply

@Pi Han Goh Good information.

Chew-Seong Cheong - 4 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...